Nodal Analysis for Coronary Artery Ischemia Diagnosis - Freitas, Samuel; Ramos, Gabriel; Schmith, Jean; Costa, Cristiano (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2020: Anais do XX Simpósio Brasileiro de Computação Aplicada à Saúde, 2020)
A cardiac ischemia is a restriction of the blood flow in the heart muscle caused by narrowed heart arteries. The most common narrowing process is called atherosclerosis. The strategies to evaluate its significance are the Fractional Flow Reserve (FFR) and the Quantitative Flow Ratio (QFR) which evaluate the local impact of the atherosclerosis. This work presents a novel approach for ischemia diagnosis based on linear nodal analysis, which enables the evaluation of the whole coronary system. Even with limited variables, this method is able to indicate and quantify the impacts of a stenosis in other coronary segments than the constricted artery itself. Empirical results have shown that a left coronary artery (LCA) stenosis increases the blood flow in the left circumflex artery (LCX) together with a normal flow decrease in the left main stem (LMS), which provides secondary narrowing impact evidences. These results can complement the current techniques and increase the diagnosis assertiveness.